qanda-logo
search-icon
Symbol
Problem
solution-image
$3$ $\right)$ $\dfrac {2} {x-3}+\dfrac {x-5} {x-1}=1$ $b\right)$ $\dfrac {x+3} {x+1}+\dfrac {x-2} {x}=2$ – c) $\right)$ $\dfrac {x-6} {x-4}=\dfrac {x} {x-2}$ d) $\right)$ $1+\dfrac {2x-5} {x-2}-\dfrac {3x-5} {x-1}=0$ $e\right)$ $\dfrac {x-3} {x-2}-\dfrac {x-2} {x-4}=3\dfrac {1} {5}$ $f\right)$ $\dfrac {x-3} {x-2}+\dfrac {x-2} {x-4}=-1$ $g\right)$ $\dfrac {3x-2} {x+7}=\dfrac {6x+1} {2x-3}$ $h\right)$ $\dfrac {x+1} {x-2}-\dfrac {x-1} {x+2}=\dfrac {2\left(x^{2}+2\right)} {x^{2}-4}$
Algebra
Search count: 184
Solution
answer-user-profile-image
Qanda teacher - Hemanth
answer-reply-image
answer-reply-image
answer-reply-image
answer-reply-image